Social Cognition and Disinformation: A Psychosocial Reading of the Ratna Sarumpaet Case - Lena, Pratika Martha; D, Vita Balqis; Yosia, Sherin; Lusianawati, Hayu (West Science Social and Humanities Studies, 2025)
This study aims to analyze the dynamics of social cognition in the case of public deception committed by Ratna Sarumpaet in 2018. Using a qualitative case study approach and a social cognition theoretical framework, this study examines how the public forms perceptions, makes social attributions, and how cognitive schemas and biases play a role in responding to narratives presented by public actors. The analysis reveals that public acceptance of false narratives is significantly influenced by existing social schemas, confirmation bias, representative heuristics, and social identity factors. This case underscores the importance of understanding social cognition processes in the digital age, where information spreads rapidly and perceptions are shaped within social interaction spaces saturated with emotions and ideological interests. This study recommends strengthening media literacy and developing critical awareness as preventive measures against disinformation and public opinion manipulation.